Opportunities for Introduction of a Mentoring Program in the Training of Doctoral Students in the Field of Defense and Security Economics - Bozmarova, Adela (Research Papers, 2022)
Training through a mentoring approach is establishing itself as an increasingly key and effective model for working with young people, which, in addition to increasing the solid knowledge of learners, plays a key role in building and consolidating specific professional and soft skills. The relevance of this study is determined by the common challenges associated with the retention, perseverance and completion of the educational and scientific degree "PhD" both at home and abroad. In this regard, focusing on the work of a particular department, the goal of this study is after analyzing the foreign experience to offer an alternative to improve training in the PhD program in economics and management (defense and security) of UNWE. The method that will be used in the present study is the analysis of foreign experience and good practices, as well as comparative analysis. The result that is expected to be achieved is to identify working alternatives in the context of the training of doctoral students in the field of defense and security economics, to outline the pros and cons of both alternatives and to suggest the best option.